The Pengaruh Model Pembelajaran Inkuiri Terhadap Kemampuan Berpikir Kritis Siswa Kelas X SMAN 60 Jakarta - Firdaus, Salwaa Aulia; Hotimah, Oot; A'Rachman, Fauzi Ramadhoan (Peneliti.net, 2023)
The research aims to determine the effect of the inquiry learning model on the critical thinking skills of class X students at SMAN 60 Jakarta on atmosphere material. This research is included in the quasi-experimental design with nonequivalent control group design. The sampling technique used purposive sampling. Class X7 as an experimental class that applies the guided inquiry learning model and X5 as a control class that does not apply the guided inquiry learning model. The research data were obtained from observation, pre-test and post-test in essay form. Data analysis techniques in this study include instrument testing, analysis requirements testing, and hypothesis testing. The test results stated that the instrument was valid and reliable, and the data was normally distributed and homogeneous. The results of the Independent Sample T-Test test obtained the value of Sig. 0.014 < 0.05 which means Ho is rejected and Ha is accepted. So that there are differences in the critical thinking skills of students in class X7 who apply the inquiry learning model with class X5 who do not apply the inquiry learning model to atmospheric material.